First-in-Class ERK1/2 Inhibitor Ulixertinib (BVD-523) in Patients with MAPK Mutant Advanced Solid Tumors: Results of a Phase I Dose-Escalation and Expansion Study - Sullivan, Ryan J; Infante, Jeffrey R; Janku, Filip; Wong, Deborah Jean Lee; Sosman, Jeffrey A; Keedy, Vicki; Patel, Manish R; Shapiro, Geoffrey I; Mier, James W; Tolcher, Anthony W; Wang-Gillam, Andrea; Sznol, Mario; et al. (Cancer discovery, 2018)
Ulixertinib (BVD-523) is an ERK1/2 kinase inhibitor with potent preclinical activity in BRAF- and RAS-mutant cell lines. In this multicenter phase I trial (NCT01781429), 135 patients were enrolled to an accelerated 3 + 3 dose-escalation cohort and six distinct dose-expansion cohorts. Dose escalation included 27 patients, dosed from 10 to 900 mg twice daily and established the recommended phase II dose (RP2D) of 600 mg twice daily. Ulixertinib exposure was dose proportional to the RP2D, which provided near-complete inhibition of ERK activity in whole blood. In the 108-patient expansion cohort, 32% of patients required dose reduction. The most common treatment-related adverse events were diarrhea (48%), fatigue (42%), nausea (41%), and dermatitis acneiform (31%). Partial responses were seen in 3 of 18 (17%) patients dosed at or above maximum tolerated dose and in 11 of 81 (14%) evaluable patients in dose expansion. Responses occurred in patients with -, V600-, and non-V600 -mutant solid tumors. Here, we describe the first-in-human dose-escalation study of an ERK1/2 inhibitor for the treatment of patients with advanced solid tumors. Ulixertinib has an acceptable safety profile with favorable pharmacokinetics and has shown early evidence of clinical activity in - and V600- and non-V600-mutant solid-tumor malignancies. .